[Construction view of equipment and crane for the Library] - P. K. Phillips::::::photographer::: (1978)
View of the equipment used to build Kennedy Library, facing north. Construction workers stand around the machine used to construct the crane. The parking lot adjacent to Kennedy Library is full of cars.